Supramolecular architecture of [AsPh2Br2]2[(Br3)−…(Br2)…(Br3)−] obtained by bromination of (AsPh2)2S - Silaghi-Dumitrescu, Luminita; Attia, Amr A.A.; Silaghi-Dumitrescu, Radu; Blake, Alexander J.; Sowerby, D. Bryan (Elsevier, 2017)
Bromination of (AsPh2)2S leads to cleavage of the sulfide bridge to give AsPh2Br when 1 mol of bromine is used but with 2 mols the product is the polybromide, [AsPh2Br2]2[Br8], containing the previously unknown [AsPh2Br2]+ cation and a rare [(Br3)−…(Br2)…(Br3)−] ensemble whose short (yet not covalent) Br2…Br3 contacts have previously supported tentative description as an octabromide Br82− anion. X-ray crystallography shows that the compound has a three dimensional supramolecular structure based on cooperativity of weak intermolecular Csingle bondH…π, Csingle bondH…Br hydrogen bonds and secondary Br…Br interactions in the solid state. The electronic structure and the stability of the [AsPh2Br2]2[Br8] are rationalized using DFT and HF calculations and molecular orbital considerations.